The windvane self-steering handbook - Morris, Bill (Bill V.) (International Marine/Mcgraw-hill, 2004)
Here is the definitive manual for choosing, purchasing, installing, maintaining, repairing, using, and even building a windvane self-steerer, that amazing device that relieves longdistance sailors from the the helm while using not one amp of precious electrical power.